Colloidal surface-enhanced Raman spectroscopic study of grouper epidermal mucus using acidified sodium sulphate as the aggregating agent - Leong, Nathaniel; Yaacob, Mohd Hanif; Md Zain, Ahmad Rifqi; Tengku Abdul Aziz, Tengku Hasnan; Christianus, Annie; Chong, Chou Min; Mahdi, Mohd Adzir (Elsevier BV, 2024)
Fish epidermal mucus is an important reservoir of antipathogenic compounds which serves as the first line of the immune defence. Despite its significant role in the physiology and health of fish, detailed profiling of fish epidermal mucus has yet to be explored. Therefore, this study investigates a label-free colloidal surface-enhanced Raman spectroscopic (SERS) method for profiling grouper mucus. Gold nanoparticles were first synthesised using the standard citrate reduction and characterised using ultraviolet–visible spectroscopy, transmission electron microscopy and dynamic light scattering. The influence of acidified sodium sulphate (Na2SO4) at pH 3 as the aggregating agent on the enhancement of the SERS spectrum of different analyte samples including rhodamine 6G (R6G) dye, lysozyme solution and hybrid grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) mucus was observed. Based on the results, an optimal Na2SO4 concentration of 1 M was recorded to achieve the highest enhancement of the SERS signal for R6G and grouper mucus, while the optimal concentration for lysozyme was 0.1 M. The results indicated a higher degree of aggregation induced by lysozyme than R6G and grouper mucus. A few overlapping peaks of the SERS spectra of lysozyme and grouper mucus made it possible to confirm the presence of lysozyme as potential biomarkers.